SURVEI PERILAKU PSN DAN SANITASI LINGKUNGAN PADA DESA ENDEMIK FILARIASIS DI KABUPATEN BLORA - Fuad Alhamidy; Andri Sukeksi; Didik Sumanto (JURNAL LITBANG, 2006)
Background : Tke spread af filariasis disease can be control if the society lmow the procedure to avoid contact with infecler vector. Mosquite population as a infecter vector can be control by us with knowledge of fight the focus mosquite action. Mosquite control at the several area influenced by envirounment sqnitation, while lhe envirounment sanitation influenced by human action to manage it.Objective: To survey offight thefocus of mosquite action on society and observed the envirounment sanitation that corelated withfocus of mosquite plqce on Tawangrejo village on Blora.Method : population of this research is all of peoples on Tawangrejo village on Blora. Accidental sampling applied to take sample research. All of peoples that present in the healthy instruction as a sample research. To tqke the data of fight the focus mosquite used the questioner, while the observation done to observed the envirounment sanitation bydirect procedure on filariasis endemic village.Result : Among of 83,9 ok responden have offight thefocus mosquite action with ' baik ' predicqte. So on rotation of ' cukup ' and ' buruk ' is 1,7 96 and 14,4 %.Conclusion : Almost of all of the responden have of fight the focus mosquite action with 'baik' predicate, so must befound the other caused ofspread offilariasis on Tawangrejo village.Key words : The fight of the focus of mosquite action, sanitation, filariasis